Neutropenia in Children Treated With Ketogenic Diet Therapy. (June 2021) - Munro, Kristen; Keller, Anne E.; Lowe, Helen; Ferrara, Enza; Whitney, Robyn; Liu, Christiana Y. M.; Zak, Maria; Chan, Valerie; Kobayashi, Jeff; Donner, Elizabeth J.
Objectives: The objectives were to investigate the relationship between ketogenic diet therapy and neutropenia in children with epilepsy. Methods: A retrospective chart review of children who initiated ketogenic diet at the Hospital for Sick Children between January 1, 2000, and May 1, 2018 was performed. Factors associated with the development of neutropenia during ketogenic diet therapy were evaluated and the relationship between development of a significant or suspected infection and neutrophil count was analyzed. Results: One hundred two children met inclusion criteria and were followed on the diet for up to 24 months. Thirteen of 102 (13%) children were neutropenic at diet initiation. In the remaining 89 children, 27 developed neutropenia. Developing neutropenia was significantly associated with the ketogenic diet at 6 (13%), 12 (23%), and 24 (25%) months follow-up. Developing neutropenia was associated with higher urinary ketones (OR = 4.26, 95% CI: 1.27, 14.15) and longer duration of ketogenic diet therapy (OR = 3.29, 95% CI: 1.42, 7.96). There was no significant association between development of a clinically significant infection and neutropenia. Conclusion: Ketogenic diet therapy is associated with neutropenia in children with epilepsy, however, it does not have a significant clinical impact. Concern regarding neutropenia should not discourage the use of the ketogenic diet in children.